Estimation model of plagiarism of the program code based on version control system - Киричек, Галина Григорівна; Киричек, Олександр Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
The expanding functions of the estimation system of identity program code in the study and practical application of programming languages ​​in the learning process through the use of generated repositories distributed version control system are proposed